Assessment of the impact of oil and gas resource exploration on the environment of selected communities in Delta State, Nigeria - Christiana Kayinwaye Omorede (International Journal of Management, Economics and Social Sciences (IJMESS), 2014)
This Paper assessed the "Impact of Oil and Gas Resource Exploration on the Environment" of Delta State oil producing communities of Nigeria. It examined the problems associated with Oil exploration and its mitigation. Primary and Secondary data were used to source data for the set objectives. The theoretical framework was based on the resource curse theory and the environmental externalities theory. It was established that various problems such as oil spillage, retardation of vegetation growth, soil infertility, ill-health to members of the community, displacement of the people of the area, constant protestation of host communities, socio-economic deprivation, and perceived marginalization of the people are associated with oil resource exploration. This research concludes that the oil bearing communities have not adequately been compensated for harm done them through degradation of the ecosystem caused by several years of oil exploration. Their oil resource wealth has been turned to oil resource curse as they are disempowered, and condemned to perpetual underdevelopment. It is recommended that Federal Government should exert maximum efforts in assuring strict compliance of its legal instruments by the oil participating industries for a sustainable development in the region.
Keywords: H23; K32; N57; P28; 330; Oil and gas exploration; environment; community development; Delta State; Nigeria; Africa